Bond of epoxy-coated steel bars to seawater sea sand recycled concrete. (April 2021) - Huang, Yijie; Zhang, Yijian; Li, Xiaowei; Ying, Jingwei
Abstract: The bonded behaviour between epoxy-coated steel bars (ECSB) and seawater sea sand recycled concrete (SSSRC) were systematically analysed using pull-out tests. Five different parameters were considered: including types of concrete (SSSRC, recycled concrete and ordinary concrete) and steel bars (ECSB and ordinary steel bars (OSB)), the ratio of bond length to bar diameter (3, 5 and 8), and concrete strength (C20 and C25) and thickness of concrete cover (42 mm and 67 mm). The failure pattern, bond strength and bond-slip curve of specimen were analysed. The results indicate that the failure mode of specimen was pull-out failure, and the concrete type changed the failure surface of specimen. The specimen with OC exhibited high bond strength compared to specimen with SSSRC. Increasing concrete cover thickness increased the bond strength of seawater sea sand recycled concrete-ECSB (SSSRC-ECSB), while its bond strength decreased with the increase in the bond length. It can be found that the bond-slip curve of SSSRC-ECSB was similar to that of ordinary concrete-OSB (OC-OSB). SSSRC and ECSB obviously reduced the curvature of bond-slip curve, and the decline of curve changed with the types of concrete and steel bars used. Finally, a general expression of bond-slip curve was derived, which could provide a basis for the practical application of SSSRC.